Pony Express special delivery - Gibson, Rhonda (Gibson, Rhonda. Saddles and spurs., 2017)
"Pony Express manager Clayton Young arrives for his new assignment at a Wyoming ranch just in time to save Maggie Fillmore's ailing baby. The lovely young widow is struggling to care for a ranch, her sister and a newborn, and Clayton plans to pursue medicine--not marriage. Yet Maggie's dire situation spurs him to offer a match of convenience... Maggie hoped never to rely on any man again, even one as kind as Clayton. But with her late husband's greedy cousin trying to take away her ranch, she has little choice. And though Maggie worries her union with Clayton might not be enough to save her ranch, she soon sees it could be just what her heart needs." -- Page [4] cover.